DEVELOPMENT OF AIM/END-USE MODELS FOR SELECTING LOW CARBON TECHNOLOGY OF IRON DAN STEEL INDUSTRY SECTORS - Navira Sevie, Gissa
As an intensive energy-consuming and carbon emitting in industry sector, iron and steel industry plays an important role to achieve the target of Indonesia's commitment towards the direction of low-carbon development. In this study, a quantitative evaluation was conducted to analyze the effectiveness of emissions mitigation on potential energy saving and carbon emission reduction using the bottom up AIM/end-use energy model in 2010-2050. Several energy models have been proposed previously to quantify carbon emission. However, a separate analysis of emissions from energy usage and IPPU (Industrial Process and Product Use) has never been done. The energy model is built under the baseline scenario and the following relevant mitigation scenario options were investigated: (i) adjusted the production structure, by increasing material efficiency with the scrap use in steel production process BF-BOF (Blast furnace-Basic oxygen furnaces) route and scrap -EAF (Electric arc furnace) route (CM1 scenario), (ii) maximized energy efficiency, by promoting low carbon technology and non-blast furnace technology (smelting reduction) that is unimplemented early in modeling years in Indonesia will be included in the energy model for future reference (CM2 scenario), (iii) carbon emissions reduction through substitution of fossil fuels to low emission fuels (CM3 scenario). Based on the assumption 15 million tons of Indonesia's steel production projection in 2050. In ACC tools for carbon tax 110 USD/ton CO2e, obtained roadmap of selected technology with emission reductions potential 19.8 million tons of CO2e, 50.2 million tons CO2e, 54.84 million tons of CO2e with mitigation costs 93.55 million USD, 1086 million USD, and 1183 million USD in the scenarios CM1, CM2 and CM3, respectively. The effectiveness analysis of each mitigation actions in the AIM /end-use model shows that increasing scrap utilization provides the most significant reduction in IPPU emissions (0.37 tons CO2e/tonne of steel). Promotion of low-carbon technology is the main driver for GHG emissions in energy activities reduction with a potential reduction of 2.50 tons of CO2e/tonne of steel in 2050. While substitution of fossil fuels to low emission fuels smallest constribution to reduce emissions related to energy (0.185 tons CO2e/ton of steel) compared with other scenarios.